Tinjauan Siyasah Dusturiyah Terhadap Pelaksanaan Peraturan Daerah Kota Jayapura Nomor 12 Tahun 2007 Tentang Pengawasan Kualitas Air(Studi Khusus Retribusi Pengelolaan Air di Kelurahan Entrop Jayapura Selatan Kota Jayapura) - Indah Nur Madaniah Latulusi; Zulfadli Zulfadli; Sabar Podu; Rahma Anugraheny; Lukman Ansar (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2026)
This study examines the implementation of Jayapura City Regional Regulation Number 12 of 2007 on Water Quality Supervision in the management of a water source in Entrop Village and evaluates it from the perspective of siyasah dusturiyah. The study employed an empirical legal method using statutory, conceptual, and sociological approaches. Primary data were collected through non-participant observation and interviews with the manager’s assistant, a household consumer, and a water-tanker driver, while secondary data were obtained from legislation, books, journal articles, and related documents. The data were analyzed qualitatively through reduction, categorization, legal interpretation, and conclusion drawing. The findings show that the water source has been utilized and distributed to the public at a relatively affordable price; however, the supervision process has not been supported by adequate documentation concerning laboratory results, testing parameters, examination frequency, the identity of the examining institution, and follow-up measures. The levy provisions contained in Regional Regulation Number 12 of 2007 can no longer serve as the legal basis for collection because they were revoked by Jayapura City Regional Regulation Number 3 of 2012, while groundwater tax obligations must be determined under the current regulatory framework. From the perspective of siyasah dusturiyah, the management practice has fulfilled certain elements of public benefit and distributive justice, but it has not fully satisfied the principles of legal compliance, trustworthiness, transparency, accountability, public health protection, and environmental sustainability. This study recommends harmonizing government supervision, recognition of customary land rights, and administrative compliance.